THE ROLE OF NOTARIES IN THE IMPLEMENTATION OF THE LEASE PURCHASE SYSTEM AS AN ALTERNATIVE TO BUILDING OWNERSHIP IN PUBLIC HOUSING SAVINGS (TAPERA) - Pandita, Nabila Dhiya (Faculty of Law, Universitas Pekalongan, 2024)
Notaries have an active role in implementing a new system, namely lease purchase system as an alternative to transferring a new land ownership rights based on the Public Housing Savings Management Agency Regulation Number 2 of 2023 concerning the Second Amendment to the Public Housing Savings Management Agency Regulation Number 6 of 2021 concerning Housing Financing for Public Housing Savings Participants (Peraturan Badan Pengelola Tabungan Perumahan Rakyat Nomor 2 Tahun 2023 tentang Perubahan Kedua atas Peraturan Badan Pengelola Tabungan Rakyat Nomor 6 Tahun 2021 tentang Pembiayaan Perumahan Bagi Peserta Tabungan Perumahan Rakyat). This is because to be able to apply the lease purchase system in a transfer of land ownership rights, an agreement is needed which for legal certainty to be made into a deed for the parties. Departing from the above, the problem raised in this research is how to implement the lease purchase system as an alternative to financing home ownership and the role of the Notary in making a lease purchase agreement deed which is used as an alternative to transfer land ownership rights. To be able to answer these problems, a normative juridical research method with an explanatory research typology is used. The conclusion that can be drawn from this research is that notaries play an important role in implementing the hire purchase system which has just been issued by BP Tapera as an alternative to transferring land and building ownership rights. So that in order to provide legal certainty, the lease purchase agreement needs to be made in an authentic deed made by a Notary.